2023
DOI: 10.1177/07356331231175999
|View full text |Cite
|
Sign up to set email alerts
|

Understanding English as a Foreign Language Students’ Idea Generation Strategies for Creative Writing With Natural Language Generation Tools

Abstract: Natural language generation (NLG) is a process within artificial intelligence where computer systems produce human-comprehensible language texts from information. English as a foreign language (EFL) students’ use of NLG tools might facilitate their idea generation, which is fundamental to creative writing. However, little is known about how EFL students interact with NLG tools to generate ideas. This study explores strategies adopted by EFL students when searching for ideas using NLG tools, evaluating ideas ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Based on the present study, it may be possible to propose several explanations of why ChatGPT improved all three dimensions: quality, elaboration, and originality (Todd et al, 2019). As suggested by Woo et al (2023), ChatGPT may enhance divergent thinking processes by exposing students to a wide range of possible solutions. This exposure then encourages students to consider a larger pool of solutions, allowing them to select more promising prototypical solutions (Mumford et al, 1991;2019).…”
Section: Quality Elaboration and Originality Of Solutions Co-created ...mentioning
confidence: 60%
“…Based on the present study, it may be possible to propose several explanations of why ChatGPT improved all three dimensions: quality, elaboration, and originality (Todd et al, 2019). As suggested by Woo et al (2023), ChatGPT may enhance divergent thinking processes by exposing students to a wide range of possible solutions. This exposure then encourages students to consider a larger pool of solutions, allowing them to select more promising prototypical solutions (Mumford et al, 1991;2019).…”
Section: Quality Elaboration and Originality Of Solutions Co-created ...mentioning
confidence: 60%
“…In a systematic review, it was found that students are increasingly using various AI-powered writing assistance tools, including automated writing evaluation tools, corrective feedback tools, machine translators, and automatic text generators [24]. Students applied natural language generation (NLG) in creative writing and found different strategies for using NLG-generated words [25]. A study on students' perceptions of AI in a writing class found that students had positive perceptions and enjoyed using an AI app for writing [26].…”
Section: Fig 1: Literature Review From Elicit Aimentioning
confidence: 99%